Theoretical Rationale for How Slimming Garments May Motivate Physical Activity in People with Obesity. Issue 4 (June 2018) - Binks, Martin; Chin, Shao-Hua
Abstract : Obesity and inactivity contribute to disease burden and increased mortality worldwide. Consistency in initiating and maintaining adequate physical activity continues to be a major challenge. The majority of the weight loss and exercise science literature focuses on enhancing personal responsibility. For people with obesity, perceptions of others, a history of negative self-judgment and consequent low exercise self-efficacy influence the likelihood that they will engage in physical activity. We provide a theoretical rationale for the utility of slimming garments in enhancing exercise adherence. We reviewed and compiled relevant literature related to motivational theory and body image to develop a theoretical basis for the use of slimming garments to promote exercise adherence. Our review provides theoretical support for the potential for slimming garments to improve exercise adherence. Reductions in exercise avoidance may be achieved through the use of slimming garments during and following exercise.